2023
DOI: 10.14245/ns.2346132.066
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Canal Remodeling and Indirect Decompression of Contralateral Foraminal Stenosis After Endoscopic Posterolateral Transforaminal Lumbar Interbody Fusion

Abstract: Objective: There is a lack of literature on indirect decompression in uniportal endoscopic posterolateral transforaminal lumbar interbody fusion (EPTLIF). Our aim is to evaluate the dimensions of the spinal canal and contralateral foramen before and after EPTLIF.Methods: This is a retrospective study of patients who underwent EPTLIF in a tertiary spine centre over a 2-year period. The cross-sectional area of the spinal canal and the contralateral foramen at the level of fusion were measured on magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…However, no significant differences in patient-reported outcome measures (PROMs) were observed across the other CARDS classes in the univariable or multivariable analyses, leading the authors to conclude that while CARDS A patients appear to benefit from TLIF, no additional benefit of interbody placement exists in CARDS B or C patients [15]. Given that interbody placement can provide enhanced disc space restoration and indirect neuroforaminal decompression [15,22,23], the benefit of this approach among CARDS A patients is logical. Unsurprisingly, overall trends in the performance of interbody fusions are variable across CARDS groups in the current study and others given the heterogeneous nature of DLS.…”
Section: Discussionmentioning
confidence: 99%
“…However, no significant differences in patient-reported outcome measures (PROMs) were observed across the other CARDS classes in the univariable or multivariable analyses, leading the authors to conclude that while CARDS A patients appear to benefit from TLIF, no additional benefit of interbody placement exists in CARDS B or C patients [15]. Given that interbody placement can provide enhanced disc space restoration and indirect neuroforaminal decompression [15,22,23], the benefit of this approach among CARDS A patients is logical. Unsurprisingly, overall trends in the performance of interbody fusions are variable across CARDS groups in the current study and others given the heterogeneous nature of DLS.…”
Section: Discussionmentioning
confidence: 99%
“…Even those who experienced spontaneous improvement might have benefitted from surgery (e.g., less pain, potentially better neurologic recovery, etc.). Consequently, it is possible that certain patients continued to suffer from pain and disability and were unable to return to their normal lives [ 14 , 34 36 ]. With applying surgical criteria strictly to decide the necessity of elective lumbar surgeries, essential elective surgeries could be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it is possible that certain patients continued to suffer from pain and disability and were unable to return to their normal lives. 13,[34][35][36] The current study showed that the regulation of the COVID-19 pandemic in ROK did not affect the total number of elective operations, and this lesson may be useful in planning policies about spine surgery and transitioning to the "new normal" era.…”
Section: Number Of Operations Monthly Distribution and Epidemic Wavesmentioning
confidence: 99%